1997
DOI: 10.1007/s002470050258
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of renal osteodystrophy in children

Abstract: MRI is a potentially useful tool for evaluating the bone changes of renal osteodystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Olmastroni et al demonstrated in a pilot study using bone MRI (0.5 T) in a cohort of 14 children and adolescents (among them six undergoing hemodialysis and eight with CKD on conservative therapy) that there was a thickening of cortical bone in seven patients, with a thickening of trabeculae in three [28].…”
Section: Discussionmentioning
confidence: 97%
“…Olmastroni et al demonstrated in a pilot study using bone MRI (0.5 T) in a cohort of 14 children and adolescents (among them six undergoing hemodialysis and eight with CKD on conservative therapy) that there was a thickening of cortical bone in seven patients, with a thickening of trabeculae in three [28].…”
Section: Discussionmentioning
confidence: 97%
“…In patients with chronic renal insufficiency including osteosclerosis, brown tumors, skeletal deformity, fatty marrow inversion, osteonecrosis, transient bone marrow edema and occult stress fracture, MRI is helpful in the evaluation of bone marrow abnormalities (2, 3). Ito et al (5) reported that in chronic renal failure, T1 relaxation time was related to the cellular histologic findings of the vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged T1 relaxation time of the vertebrae observed in cases involving osteosclerosis was due to hypercellularity, the presence of thickened or many small irregular trabeculae, or peritrabecular fibrosis. Olmastroni et al (3) reported that the thickened irregular trabeculae in the proximal femoral metaphyses were observed in three of 14 patients with renal osteodystrophy who underwent MR. Trabecular bone thickening was clearly demonstrated by MR as very low signal intensity cortical sleeves or medullary streaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[84] patterns of ROD, but these studies drew attention to the usefulness Studies that assessed iPTH levels, bone formation and resorpof bone density monitoring during the course of treatment in a tion markers, and calcium and phosphorus levels confirmed the given patient. Other imaging methods such as magnetic limitations of precisely evaluating the osteodystrophy pattern on resonance [105] or bone scintigraphy [106] may prove to be more the basis of non-invasive examinations only. For the comprehenuseful in the assessment of and differentiation between patterns of sive evaluation of the skeletal status, it is recommended to perform bone changes in ROD.…”
Section: Radiologic Investigationsmentioning
confidence: 98%